Immune modulation induced by tuberculosis DNA vaccine protects non-obese diabetic mice from diabetes progression - dos Santos, R. Rodrigues; Sartori, A.; Bonato, V. L. Deperon; Castelo, A. A. M. Coelho; Vilella, C. A.; Zollner, R. L.; Silva, C. Lopes (Blackwell Publishing, 2007)
We have described previously the prophylactic and therapeutic effect of a DNA vaccine encoding the Mycobacterium leprae 65 kDa heat shock protein (DNA-HSP65) in experimental murine tuberculosis. However, the high homology of this protein to the corresponding mammalian 60 kDa heat shock protein (Hsp60), together with the CpG motifs in the plasmid vector, could trigger or exacerbate the development of autoimmune diseases. The non-obese diabetic (NOD) mouse develops insulin-dependent diabetes mellitus (IDDM) spontaneously as a consequence of an autoimmune process that leads to destruction of the insulin-producing beta cells of the pancreas. IDDM is characterized by increased T helper 1 (Th1) cell responses toward several autoantigens, including Hsp60, glutamic acid decarboxylase and insulin. In the present study, we evaluated the potential of DNA-HSP65 injection to modulate diabetes in NOD mice. Our results show that DNA-HSP65 or DNA empty vector had no diabetogenic effect and actually protected NOD mice against the development of severe diabetes. However, this effect was more pronounced in DNA-HSP65-injected mice. The protective effect of DNA-HSP65 injection was associated with a clear shift in the cellular infiltration pattern in the pancreas. This change included reduction of CD4(+) and CD8(+) T cells infiltration, appearance of CD25(+) cells influx and an increased staining for interleukin (IL)-10 in the islets. These results show that DNA-HSP65 can protect NOD mice against diabetes and can therefore be considered in the development of new immunotherapeutic strategies.
Keywords: cytokines; diabetes; DNA vaccine; heat shock protein (Hsp65)